DETERMINANTS INFLUENCING CROSS SELLING IN BANKS: A FACTOR ANALYSIS APPROACH - Bhullar, Narinderjit Singh; Sandhu, Vikram (International Journal of Psychosocial Rehabilitation, 2020)
Economical development of any country largely depends upon the prevalent banking scenarios which represent banks as a place, a medium to cater to various businesses dwelling around. To run any banking business customer is the most vital of all and hence it becomes imperatives to know and to study the perception of the customer. Banks not only are engaged in increasing the customer base year on year but also focus on the retention of the old customers. It is this customer base only which helps banks grow and to achieve the various deposit and cross sell targets. Banks often define their deposit targets as “NAV (new acquisition value) and CIB (Change in base)” which becomes a measure to bring new customers for NAV and to engage the old customer to solidify the previous FY base. This exercise is conducted both by the public as well as private sector banks and accordingly they choose to opt different strategies which further define the level of customer satisfaction. Since the strategies adopted are different at different banks hence satisfactions level of the customers tend to differ in these banks. This paper deals with identification and examining the various factors which prompt customer to get cross sold.